2024
DOI: 10.1186/s13098-024-01274-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of autoimmune diseases in an admixed population of patients with type 1 diabetes: a multicenter study in Brazil

Marilia Brito Gomes,
Fernanda Oliveira Braga,
Karla Guerra Drummond
et al.

Abstract: Background/objectives The primary aim of this study was to evaluate the prevalence of autoimmune diseases (AIDs) and its associated factors in an admixed Brazilian population of patients with type 1 diabetes (T1D). The secondary one was to determine the relationship between AIDs and the occurrence of diabetes-related chronic complications (DRCC). Methods This cross-sectional, nationwide survey was conducted in 13 public clinics in 11 Brazilian citi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…In an earlier study, for instance, genetic influences exhibited correlations between the two conditions, with 11% of the variance in T1DM and 9% in Hashimoto’s thyroiditis being explained by additive genetic effects common to both disorders. A recent Brazilian multicenter study, conducted on 1760 patients, found that the prevalence of autoimmune diseases among T1DM patients was 19.5%, while the prevalence of autoimmune thyroid diseases was 16.1% [ 12 ]. Furthermore, environmental factors unique to individual twins, yet shared across both diseases, contributed to 10% of the variance in type 1 diabetes and 18% in Hashimoto’s thyroiditis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, for instance, genetic influences exhibited correlations between the two conditions, with 11% of the variance in T1DM and 9% in Hashimoto’s thyroiditis being explained by additive genetic effects common to both disorders. A recent Brazilian multicenter study, conducted on 1760 patients, found that the prevalence of autoimmune diseases among T1DM patients was 19.5%, while the prevalence of autoimmune thyroid diseases was 16.1% [ 12 ]. Furthermore, environmental factors unique to individual twins, yet shared across both diseases, contributed to 10% of the variance in type 1 diabetes and 18% in Hashimoto’s thyroiditis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%